Regulating interfacial reaction through electrolyte chemistry enables gradient interphase for low-temperature zinc metal batteries - Wei Wang; Shan Chen; Xuelong Liao; Rong Huang; Fengmei Wang; Jialei Chen; Yaxin Wang; Fei Wang; Huan Wang (Nature Communications, 2023)
Abstract In situ formation of a stable interphase layer on zinc surface is an effective solution to suppress dendrite growth. However, the fast transport of bivalent Zn-ions within the solid interlayer remains very challenging. Herein, we engineer the SEI components and enable superior kinetics of Zn metal batteries under harsh conditions through regulating the sequence of interfacial chemical reaction. With the differences in chemical reactivity of trimethyl phosphate co-solvent and trifluoromethanesulfonate anions in the Zn2+-solvation shell, Zn3(PO4)2 and ZnF2 are successively generated on Zn metal surface to form a gradient ZnF2–Zn3(PO4)2 interphase. Mechanistic studies reveal the outer ZnF2 facilitates Zn2+ desolvation and inner Zn3(PO4)2 serves as channels for fast Zn2+ transport, contributing to long-term cycling at subzero temperatures. Impressively, the gradient SEI enables a high lifespan over 7000 hours in Zn symmetric cell and a capacity retention of 86.1% after 12000 cycles in Zn–KVOH full cell at –50 °C.